Grasses (Poaceae) From Senegal: New Records Checklist, Biogeographical Affinities and Biological Types - Ngom, Ablaye; Mbaye, Mame Samba; Camara, Abdoul Aziz; Gueye, Madiop; Noba, Kandioura (European Scientific Journal, ESJ, 2020)
Poaceae is one of the most diverse families in Senegal’s flora after Fabaceae. It has been the subject of several studies but many species were not taken into account in the evaluation of the current state of its diversity. This paper provides a checklist of new grasses encountered in Senegal. After a detailed scrutiny of the literature and herbarium specimens, we ascertain their identity and report them as new records to the grass flora of Senegal. A total of 24 new species have been listed belonging to 15 genera of which the most represented is Sporobolus with 5 species. The other genera such as Digitaria, Eragrostis, Perotis, Setaria, and Trichanthecium on the one hand and Aristida, Chloris, Cymbopogon, Enteropogon, Leptochloa, Oryza, Panicum, Schizachyrium, Urochloa on the other hand have two and one species respectively. The chorological spectrum shows the dominance of African species (45.83%) followed by those of Afro-Asian origin (33.33%). Like the overall flora of Senegal, this new grass flora is of tropical nature with a preponderance of Sudano-Zambesian species (50%) followed by Guinean- Congolese-Sudano-Zambesian species (29.17%) at continental scale. Biological types based on the life form shows therophytes (62.50%) are predominant, followed by hemicryptophytes (29.17%) and geophytes (8.33%). Taking these new data into account would allow a more precise determination of the Senegalese grass flora composition.